Peran Pariwisata Raja Ampat dalam Perkembangan Ekonomi Kawasan - Ery Atmodjo (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2021)
Tourism is a multi-sector industry that has the potential to induce investment, consumption, and employment opportunity. Tourists' movement from their place of origin to tourism destination may have an impact on the regional economy of transit place. This study analyses the role of tourism of Raja Ampat Regency in the economic growth of Sorong Municipality as the transit city for tourists heading for Raja Ampat Regency. The steady growth of tourism of Raja Ampat Regency plays role in the growth of tourists arrival in Sorong Municipality but has no impact on the GDRP of the tourism sector of Sorong Municipality.